2004
DOI: 10.1124/jpet.104.070995
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prostaglandins in Mediating Differences in Human Internal Mammary and Radial Artery Relaxation Elicited by Hypoxia

Abstract: The effects of hypoxia-reoxygenation on internal mammary (IMA) and radial (RA) arteries used for coronary artery bypass grafting (CABG) were examined to identify mechanisms regulating contractile function and differences that could contribute to vasospasm. Isolated endothelium-intact IMA and RA rings precontracted with KCl (30 mM) rapidly dilated to hypoxia (95% N 2 /5% CO 2 ) with a greater relaxation in RA than IMA. Inhibitors of cyclooxygenase (10 M indomethacin) and the thromboxane A 2 (TxA 2 ) -29548)] po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Frozen sections of pulmonary artery were fixed in acetone, and antigen retrieval was done with 0.1% Triton X-100 as described previously (14,15,22). After the sections were blocked by incubation for 1 h in 5% normal goat serum or 5% BSA at room temperature, they were incubated with primary antibody overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen sections of pulmonary artery were fixed in acetone, and antigen retrieval was done with 0.1% Triton X-100 as described previously (14,15,22). After the sections were blocked by incubation for 1 h in 5% normal goat serum or 5% BSA at room temperature, they were incubated with primary antibody overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…[12,13,18] Since the biosynthesis of some autacoids including nitric oxide, prostaglandins, cytochrome P450-derived eicosanoids and ROS are oxygen-dependent, these mediators often influence or modulate systemic and pulmonary responses to hypoxia. [2022]…”
Section: Oxygen Sensors In Systemic Arteries and Metabolic Mechanismsmentioning
confidence: 99%
“…Additionally, it was previously reported that RA grafts are more sensitive to TxA 2 [13]. Furthermore, it has been reported that IMAs produce substantial amounts of both PGI 2 and TxA 2 [128]; nonetheless, the TxA 2 to PGI 2 ratio was significantly higher in the RA than in the IMA. Because PGI 2 antagonizes the actions of TxA 2 , the higher TxA 2 to PGI 2 ratio implies that TxA 2 would exert greater effects in the RA.…”
Section: Radial Arterymentioning
confidence: 85%